Consensus on future research directions in the phylum Rotifera - Rafael L. Macêdo; Carlota Solano‐Udina; Melanie D. Borup; Marco Antonio Jiménez‐Santos; Cristina Arenas‐Sánchez; Christina W. C. Branco; Karen Costa; Betina Kozlowsky‐Suzuki; Cláudia C. Bonecker; Elizabeth J. Walsh; André R. S. Garraffoni; S. S. S. Sarma; et al. (Limnology and Oceanography, 2026)
Rotifers play key roles in aquatic ecosystems, yet significant uncertainty remains about their diversity and evolution, and further evidence is needed to determine how reliably their responses to global change and human impacts can inform conservation. To identify major knowledge gaps hindering progress, we carried out a Delphi process both online and during the 17 th International Rotifer Symposium, involving more than 40 experts across diverse regions and subdisciplines. A total of 133 research questions were screened for relevance and clarity and reduced to 100 for online scoring. These were evaluated on a 1‐to‐10 priority scale, after which 67 questions exceeding 50% agreement were advanced to an in‐person workshop. Through structured discussions and round‐table voting, participants identified gold, silver, and bronze priority questions, while considering the feasibility of addressing them, resulting in a final consensus set of high‐priority questions across basic, applied, and philosophical perspectives including how rotifer communities are defined, how evidence is generated and integrated, and how values shape research priorities. Support for questions on knowledge transfer, digital curation, and AI‐assisted identification highlights the emergence of a methodological subfield linking classical approaches with modern computational tools. Likewise, the emphasis on improving genetic markers and connecting DNA sequences with traits shows that molecular research is now viewed as a foundational component of rotiferology. This synthesis provides the first community‐driven roadmap for rotifer research. By articulating shared priorities and clarifying persistent knowledge gaps, including unreliable phylogenies, uneven sampling worldwide, and limited hypothesis‐driven work, it provides a foundation for future collaborative projects, funding strategies, and cross‐disciplinary integration.